2006
DOI: 10.1002/chem.200501475
|View full text |Cite
|
Sign up to set email alerts
|

Bis(oxazoline) Lewis Acid Catalyzed Aldol Reactions of Pyridine N‐Oxide Aldehydes—Synthesis of Optically Active 2‐(1‐Hydroxyalkyl)pyridine Derivatives: Development, Scope, and Total Synthesis of an Indolizine Alkaloid

Abstract: A new, short, and simplified procedure for the synthesis of optically active pyridine derivatives from pro-chiral pyridine-N-oxides is presented. The catalytic and asymmetric Mukaiyama aldol reaction between ketene silyl acetals and 1-oxypyridine-2-carbaldehyde derivatives catalyzed by chiral copper(II)-bis(oxazoline) complexes gave optically active 2-(hydroxyalkyl)- and 2-(anti-1,2-dihydroxyalkyl)pyridine derivatives in good yields and diastereoselectivities, and in excellent enantioselectivities-up to 99 % e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 111 publications
0
32
0
Order By: Relevance
“…In 2006, Jørgensen and co-workers 49 concluded the total synthesis of nonnatural indolizine alkaloid 145 (Scheme 24). For this purpose, the authors performed a Mukaiyamatype aldol reaction between silyl enol ether 142 and aldehyde 141, mediated by a chiral (S,S)-t-Bu-BOX 144, leading to the formation of the aldol adduct 143 in excellent levels of diastereo-and enantiomeric excess (Scheme 24).…”
Section: Asymmetric Induction In Mukaiyama Aldol Reactions With Bis(omentioning
confidence: 99%
“…In 2006, Jørgensen and co-workers 49 concluded the total synthesis of nonnatural indolizine alkaloid 145 (Scheme 24). For this purpose, the authors performed a Mukaiyamatype aldol reaction between silyl enol ether 142 and aldehyde 141, mediated by a chiral (S,S)-t-Bu-BOX 144, leading to the formation of the aldol adduct 143 in excellent levels of diastereo-and enantiomeric excess (Scheme 24).…”
Section: Asymmetric Induction In Mukaiyama Aldol Reactions With Bis(omentioning
confidence: 99%
“…Landa et al investigated the stereoselectivity of the Mukaiyama aldol reaction between a variety of pyridine-2-carbaldehydes and silyl enol ethers en route to the preparation of indolizidine derivatives (Scheme 4). [33] Here, it was found that oxidation of the pyridine nitrogen to the corresponding oxypyridine allowed for bidentate co-ordination to a chiral catalyst [copper triflate with (S)-tBu-BOX as chiral ligand], resulting in good anti diastereoselectivity and excellent enantioselectivity. The best result was achieved using isoquinoline-2-carbaldehyde N-oxide (28) with phenyl (benzyloxy)acetate-derived trimethylsilyl enolate 29 to give the anti aldol product 30 in high yield and with outstanding enantioselectivity.…”
Section: Aldol Reactionsmentioning
confidence: 99%
“…Di-n-butyltin dichloride and tributyltin chloride were obtained from Chemtura (Bergkamen). Dibutylphenyltin hydride [46] and 6-bromo-[1,3]-dioxolan-2-ylpyridine [63] were prepared according to the literature procedures. The polystyrene-divinylbenzene matrix (Amberlite XE-305 with diameter = 0.7 mm and pore = 90 nm) was purchased from Interchim.…”
Section: Generalmentioning
confidence: 99%